Efficacies of radiotherapy in rectal cancer patients treated with total mesorectal excision or other types of surgery: an updated meta-analysis - Wenshu Wang; Runyuan Zhao; Xi Liang; Manjun Liu; Haiyan Bai; Jianli Ge; Binxi Yao; Zheng Zhi; Jianming He; Jianming He (Oncology Reviews)
BackgroundAn updated meta-analysis was conducted to evaluate the efficacy of radiotherapy in rectal cancer patients treated with total mesorectal excision (TME) or other types of surgery (non-TME-only).MethodsThe PubMed, Cochrane Library, and CNKI databases were searched. Data on overall survival (OS) were extracted.ResultsHazard ratios (HRs) for OS associated with preoperative radiotherapy, preoperative long-course concurrent chemoradiotherapy (LCCRT), preoperative radiotherapy alone, and postoperative radiotherapy in patients treated with TME were 1.02 [95% CI: 0.92–1.14, P = 0.65], 1.04 [95% CI: 0.93–1.16, P = 0.47], 0.87 [95% CI: 0.61–1.25, P = 0.46], and 1.18 [95% CI: 0.91–1.52, P = 0.20], respectively. HRs for OS associated with preoperative radiotherapy, preoperative LCCRT, preoperative radiotherapy alone, preoperative long-course RT (LCRT), and preoperative short-course radiotherapy (SCRT) in patients treated with non-TME-only surgery were 0.85 [95% CI: 0.79–0.90, P < 0.00001], 0.77 [95% CI: 0.63–0.94, P = 0.009], 0.86 [95% CI: 0.80–0.92, P < 0.0001], 0.83 [95% CI: 0.73–0.95, P = 0.005], and 0.84 [95% CI: 0.77–0.91, P= <0.0001], respectively. The HR for postoperative radiotherapy in patients treated with non-TME-only surgery was 1.08 [95% CI: 0.84–1.39, P = 0.57].ConclusionPreoperative radiotherapy, regardless of the regimen, improves the OS in patients treated with non-TME-only surgery, but not in those treated with TME. Postoperative radiotherapy does not improve OS.Advances in knowledgeThis meta-analysis will serve as a reference for decision-making in multidisciplinary approaches for rectal cancer patients.